The Presence of Selected Russian Fictional Characters in English Detective Fiction: A Brief Overview. (3rd July 2022) - Boichuk, Igor V.; Turner, I. P.
ABSTRACT: The article deals with the stereotypical portrayal of certain Russian fictional characters in English literature from the mid-nineteenth century up to post-1991 fiction. An attempt is made to highlight particular popular tropes that recur in the characterisation of Russians or associated caricatures. Passing reference is made to other literary traditions in Western Europe, in order to establish peculiarities extant in English language cultural traditions as distinct from other contemporaneous European cultures. It is argued that during this period Russian fictional characters were mainly to be found in detective fiction, and that these would have had a more significant cultural impact, primarily due to the popularity of those authors at the time. The most representative authors in this genre – Sir Arthur Conan Doyle and Dame Agatha Christie – both write Russian characters into their work. Their depictions were influential due to their broad readership, and drew, it is argued, from cultural stereotypes popular in their day. The repetition and re-depiction of familiar characters in crime fiction bring about tropes that are drawn on in the production of theatre and film. A selection of these tropes is apparent in nearly all significant works of English language fiction. Many of them are perceived as negative, while few, if any, are on the positive side. Cultural peculiarities are exploited as plot devices. One enduring feature of the works analysed here, is the phenomenon of 'fake' Russians. The implications of the stereotypes depicted here go far beyond detective fiction.